PENERAPAN ALGORITMA RIVEST SHAMIR ADLEMAN (RSA) UNTUK MENGAMANKAN DATABASE PROGRAM KELUARGA HARAPAN (PKH) - Andika Cahya Putra; Magdalena Simanjuntak; Nurhayati Nurhayati (STMIK KAPUTAMA, 2021)
To maintain security, encryption techniques are used so that the confidentiality of the data is guaranteed. One of the encryption algorithms that is often used is the RSA (Rivest Shamir Adleman) algorithm. On this occasion the author is interested in studying the sql server database security application. In this study, the RSA (Rivest Shamir Adleman) algorithm is used to protect the PKH (Family Hope Program) database. The system will generate public keys and private keys. To secure the PKH database is encrypted with a public key. All data will be encrypted, while the private key will decrypt or restore the original state with the RSA algorithm. The application of the RSA cryptographic algorithm is a good solution for the sql server database security system that will be used to secure the PKH database. To ensure the confidentiality of PKH data stored in the database, by using the RSA algorithm into the system, the data is stored in the database so that the contents of the data cannot be understood by other parties.